What Is the Current Development Status of Character Education? Based on Seven Educators and Nearly Three Years of Literature Research: Character Education Research - Lingmin Zhang (Journal of General Education and Humanities, 2023)
To have a deeper and more comprehensive understanding of the status quo of character education, to improve the citizens' character cultivation, and achieve better development of citizens, this paper has carried out a study on character education. This study uses the literature research method, experience summary method, and qualitative analysis method. First, it analyzes the ideas on character education by seven famous educators (Plato, Aristotle, Sukhomlinsky, Kohlberg, Albert Bandura, Bertrand Russell, and Thomas Lickona). Then, through Springer and CNKI (China National Knowledge Internet), we searched the academic literature on character education in 2020, 2021, and 2022. Understand the development process, the latest progress, and quality education problems by analyzing the current theoretical research results. The findings are as follows: in the current research on quality education, educators have put forward some relatively complete theories, but the actual effect may not be perfect; According to the three years of theoretical research, these results did not reasonably apply to the quality education practice. This research has theoretical and practical significance for the future development of character education and for improving the academic system of quality education.